2022
DOI: 10.3390/en15145095
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Study on Thermo-Hydraulic Performance of NACA Airfoil Fin PCHEs Channels

Abstract: In this work, a discontinuous airfoil fin printed circuit heat exchanger (PCHE) was used as a recuperator in a micro gas turbine system. The effects of the airfoil fin geometry parameters (arc height, maximum arc height position, and airfoil thickness) and the airfoil fin arrangements (horizontal and vertical spacings) on the PCHE channel’s thermo-hydraulic performance were extensively examined by a numerical parametric study. The flow features, local heat transfer coefficient, and wall shear stress were exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Airfoil thickness plays a role in improving the crossflow heat exchanger compactness. Increasing XX from 20 to 30 contributed to enhancing the heat transfer at the leading edge because the increase of the frontal areas leads to a jet flow effect [14]. However, a slight fall was observed with further increase to 40 as large thickness causes high-intensity reverse flow at the trailing edge.…”
Section: Effects Of Airfoil Tube Geometrymentioning
confidence: 98%
“…Airfoil thickness plays a role in improving the crossflow heat exchanger compactness. Increasing XX from 20 to 30 contributed to enhancing the heat transfer at the leading edge because the increase of the frontal areas leads to a jet flow effect [14]. However, a slight fall was observed with further increase to 40 as large thickness causes high-intensity reverse flow at the trailing edge.…”
Section: Effects Of Airfoil Tube Geometrymentioning
confidence: 98%
“…Theoretical analysis [13], experimental tests [14,15], numerical simulation [16,17], and other methods are commonly used to study heat exchangers. Some scholars use three-dimensional numerical simulation methods to conduct the calculation of straight channel [18][19][20][21], Zigzag channel [22][23][24][25], S-shaped fins channel [26][27][28][29], and airfoil fins channel [30][31][32][33] structures and obtained detailed temperature and velocity fields. Straight channels have a simple structure but poor heat transfer performance.…”
Section: Introductionmentioning
confidence: 99%
“…Tian et al [30] investigated the comprehensive performance of PCHEs with eight different configurations using supercritical LNG as the working fluid and found that asymmetric fins had better heat transfer performance compared to symmetric fins. Wang et al [31] investigated the effects of airfoil fin geometric parameters (curvature, position of the maximum curvature, and thickness) and their arrangement (horizontal and vertical spacings) on the thermo-hydraulic performance of a PCHE. Accordingly, they found that the airfoil fin thickness had the largest effect on the thermal-hydraulic performance, followed by the curvature and longitudinal spacing.…”
Section: Introductionmentioning
confidence: 99%